A comet engulfs Mars: MAVEN observations of comet Siding Spring's influence on the Martian magnetosphere. Issue 21 (5th November 2015) - Espley, Jared R.; DiBraccio, Gina A.; Connerney, John E. P.; Brain, David; Gruesbeck, Jacob; Soobiah, Yasir; Halekas, Jasper; Combi, Michael; Luhmann, Janet; Ma, Yingjuan; Jia, Yingdong; Jakosky, Bruce
Abstract: The nucleus of comet C/2013 A1 (Siding Spring) passed within 141, 000 km of Mars on 19 October 2014. Thus, the cometary coma and the plasma it produces washed over Mars for several hours producing significant effects in the Martian magnetosphere and upper atmosphere. We present observations from Mars Atmosphere and Volatile EvolutioN's (MAVEN's) particles and field's instruments that show the Martian magnetosphere was severely distorted during the comet's passage. We note four specific major effects: (1) a variable induced magnetospheric boundary, (2) a strong rotation of the magnetic field as the comet approached, (3) severely distorted and disordered ionospheric magnetic fields during the comet's closest approach, and (4) unusually strong magnetosheath turbulence lasting hours after the comet left. We argue that the comet produced effects comparable to that of a large solar storm (in terms of incident energy) and that our results are therefore important for future studies of atmospheric escape, MAVEN's primary science objective. Key Points: Comet Siding Spring's coma and plasma engulfed Mars on 19 October 2014 The comet's plasma very likely severely distorted the Martian magnetosphere The comet might have driven atmospheric escape like a strong solar storm